IELTS Reading : Recent Actual Tests 2007 - 2011. (Nxb. Tổng hợp Tp.HCM : Nhân Trí Việt, 2012)
List of Reading Passages and their Test Dates;Test 1: William Gilbert anf Magnetism, The 2003 Heatwave, Amateur Naturalists; Test 2:How to Spot a Liar?Being Left - handed in a Right - handed World, What Is a Dinosaur?; Test 3:Learning by Examples, A New Ice Age, The Fruit Book; Test 4:The Mozart Effect, The Ant and the Mandarin, Music: Language We All Speak; Test 5:Wonder Plant, Children's Literature; Test 6:The Sweet Scent of Success, Mrs. Carlill and the Carbolie Smoke Ball, Communicating Styles and Conflict; Test 7:New Zealand Seaweed, Optimism and Health, The Columbian Exchange; Test 8:Going Bananas, Coastal Archaeology of Britain, Travel Books.